151k views
0 votes
Look at the image below forr the question please show step by step

Look at the image below forr the question please show step by step-example-1
Look at the image below forr the question please show step by step-example-1
Look at the image below forr the question please show step by step-example-2
User Pyrocater
by
5.3k points

1 Answer

3 votes

Solution:

Given the equation:


v=(r-s)/(2)

To solve for the variable r,

step 1: Multiply both sides by 2.

This gives


\begin{gathered} 2* v=2*(r-s)/(2) \\ \Rightarrow2v=r-s \end{gathered}

step 2: Add s to both sides of the equation.

Thus, we have


\begin{gathered} s+2v=r-s+s \\ \Rightarrow r=2v+s \end{gathered}

Hence, we have


r=2v+s

The correct option is

Look at the image below forr the question please show step by step-example-1
User Gnanz
by
4.9k points